EVALUATION OF THE INFLUENCE OF SALTED COUPLED SOILS ON ELUTION - Eshev, Sobir; Mamatov, Nurbek; Bobomurodov, Furqat; Usmonov, Rivoj; Makhmudov, Umidullo (Innovatsion texnologiyalar, 2023)
Based on the results of experimental studies, the article presents a methodology for assessing the resistance to erosion of a pre-locked saline soil, taking into account the degree of salinity of the soil. The influence of preliminary locking of different degrees of soil salinity on its intensity of erosion is considered. The dependence of the average flow velocity on the intensity of soil erosion was also established.